Photonic Crystal Phosphors Integrated on a Blue LED Chip for Efficient White Light Generation. Issue 3 (30th November 2017) - Lee, Jongho; Min, Kyungtaek; Park, Yeonsang; Cho, Kyung‐Sang; Jeon, Heonsu
Abstract: Following the proof‐of‐concept experiment in the unit structure level, photonic crystal (PhC) phosphors—structurally engineered phosphor materials based on the nanophotonics principles—are integrated with a blue light‐emitting diode (LED) chip to demonstrate a compact and efficient white light source. Red‐ or green‐emitting CdSe‐based colloidal quantum dots (CQDs) are coated on a Si3 N4 thin‐film grating to fabricate PhC phosphors. The underlying PhC structure is designed such that the photonic band‐edge modes at the zone center ( k ∣∣ = 0) are tuned to the energy of the blue excitation photons. By progressively stacking the PhC phosphor plates on a blue LED chip, the blue, green, and red emission intensities can be tightly controlled to obtain white light with the desired properties. The chromaticity coordinates, (0.332, 0.341), and correlated color temperature, 5500 K, are obtained from a stack of 3 red and 11 green PhC phosphor plates; in contrast, a stack of 5 red and 16 green reference phosphor plates are required to generate a similar white light. Overall, the PhC phosphors produce 8% higher total emission intensity out of 33% less amount of CQDs than the reference phosphors. Abstract : An efficient white light source using structurally engineered phosphors is demonstrated. Photonic crystal phosphor structures composed of red and green colloidal quantum dots are stacked on a blue light‐emitting diode chip. When photonic band‐edge modes are in resonance with the energy of blue excitation photons, white light of an intensity exceeding that from the reference device is generated, yet with a significantly reduced amount of phosphor materials.